2019
DOI: 10.1590/0100-6991e-20192211
|View full text |Cite
|
Sign up to set email alerts
|

Implementação de um modelo de triagem cirúrgica para casos urgentes em um hospital terciário.

Abstract: RESUMO Objetivo: avaliar a aplicabilidade do sistema de classificação de cores "Timing of Acute Care Surgery" (TACS) em um hospital público terciário de um país em desenvolvimento. Métodos: estudo longitudinal, retrospectivo, de um único centro, de março a agosto de 2016 e o mesmo período em 2017. Optou-se pela seleção de quatro especialidades cirúrgicas com alta demanda de urgências, as quais foram previamente treinadas sobre o sistema TACS. Para comparação com as classificações prévias de urgência e emergê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(5 reference statements)
0
4
0
3
Order By: Relevance
“…The validity of the TACS classification system was evaluated in a tertiary public hospital of a developing country, and data showed that TACS rating improves time for surgeries classified as yellow (ideal time to surgery within 6 h) [38].…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%
“…The validity of the TACS classification system was evaluated in a tertiary public hospital of a developing country, and data showed that TACS rating improves time for surgeries classified as yellow (ideal time to surgery within 6 h) [38].…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%
“…The territorial distribution of transplants can be analyzed in Figures 2, 3 These values may be linked to the risk of life and/or risk of loss of the donated organ, thus requiring the surgical procedure to occur quickly compared to the elective procedure. It is worth mentioning that the expected period between removal of the body and transplantation must take up to 48 hours, and depending on the individual's clinical condition, it requires less time than expected (Coelho et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study in a tertiary hospital which implemented TACS classification in daily routine for 4 surgical specialties with high demand for emergencies demonstrated that the TACS classification significantly improved the timing of surgery in the yellow class and during the night [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the advantages of the implementation of TACS in clinical practice, mostly in terms of reduced time from admission to the management of surgical patients in the emergency setting [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%